Analisis Perbandingan Biaya Transaksi dan Persepsi Peminjam Terhadap Prosedur Pinjaman Kredit pada Lembaga Keuangan - Novita Prima Sari; Ahmad Rifai; Didi Muwardi (JIP ( Jurnal Industri dan Perkotaan ), 2020)
Financial institutions have many forms, procedures and types, but not all financial institutions can ease the community's economy. There are still many financial institutions that make it difficult and burdensome for the people's economy. Before getting a loan the borrower must go through various procedures that have been set. This research was conducted with the aim of identifying the components of transaction costs, analyzing the value of transaction costs, comparing the total transaction costs imposed on each financial institution and analyzing the borrowers' perceptions of credit loan procedures in Bunga Raya Village, Bunga Raya District, Siak Regency. The village has three financial institutions namely BUMKam Bungaraya, UPK Maju Bersama Bungaraya and BRI Bank Raya Raya units. Descriptive analysis is used to identify components and calculate transaction cost values. Transaction cost analysis is used to compare the analysis of transaction cost. Analysis of borrower's perception is measured using an ordinal scale, which is guided by the Likert's Summated Rating Scale (LSRS). The results of the study explained that there were differences in the components and magnitude of transaction costs at each financial institution in Bunga Raya Village. The smallest total transaction costs are the BRI Bank Bunga Raya unit and the borrower's perception of the BUMKam Bungaraya credit loan procedure gets an average score in the good category, UPK Maju Bersama Bungaraya has a good average score and the BRI Bank Bunga Raya Unit has an average average score.